Understanding Reciprocity Among University Students in Low-Resource Settings: Validation and Measurement Using a Mixed-Methods Approach - AbuAlSamen, Mahmoud M.; El-Elimat, Tamam (Frontiers in Public Health, 2022)
Objectives This study aimed to investigate reciprocity among university students in low-resource settings using a convergent mixed-methods approach in Jordan. The study operationalized the effort-reward imbalance (ERI) model which is a sociological framework used to predict occupational-related health outcomes. The basic theory of ERI model assumes that an imbalance of effort and reward predicts adverse health outcomes. Methods The research involved two studies, Study I (n = 833) to quantitatively measure ERI and Study II to collect qualitative data (n = 44) on the drivers of ERI among university students. In Study I, a modified Arabic version of the ERI questionnaire was used. The study measured ERI and investigated the reliability and validity of the Arabic version of the ERI model questionnaire. In Study II, data were collected from focus groups and personal interviews and thematic analysis was used. Results The results suggested that ERI was associated with poor academic performance (OR=2.31, 95% CI 1.60–3.32), absenteeism (OR=1.66, 95% CI 1.21–2.27), low exercise level (OR=2.02, 95% CI 1.49–2.74) and poor self-reported health (OR=1.12, 95% CI 1.08–1.30). Three major themes emerged, namely high academic load, financial pressures and negative influence on the students' performance, wellbeing and health to explain effort-reward imbalance. Conclusions Results suggest that ERI among university students is multi-faceted and is not bound only to academic-related demands and that the extrinsic factors such as the economic context of Jordan is among drivers of ERI.